2017
DOI: 10.1080/23723556.2017.1373889
|View full text |Cite
|
Sign up to set email alerts
|

Ionic signalling and mitochondrial dynamics

Abstract: In age-related diseases, rise in intracellular reactive oxygen species (ROS) causes fragmentation of mitochondrial network. Our recent study demonstrated that ROS activation of TRPM2 (transient receptor potential melastatin-2) channels triggers lysosomal Zn release that, in turn, triggers mitochondrial fragmentation. The findings provide new mechanistic insights that may have therapeutic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Zinc causes mitochondrial morphology changes such as mitochondrial fragmentation, evidenced by the formation of small, round mitochondrial puncta [ 238 , 239 , 240 , 241 ]. Zinc impairment of fusion–fission dynamics likely plays an important role in causing these morphological changes, as mitochondrial fragmentation and elongation are caused by excess fission and fusion, respectively [ 217 , 219 ].…”
Section: Zinc and Mitochondrial Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc causes mitochondrial morphology changes such as mitochondrial fragmentation, evidenced by the formation of small, round mitochondrial puncta [ 238 , 239 , 240 , 241 ]. Zinc impairment of fusion–fission dynamics likely plays an important role in causing these morphological changes, as mitochondrial fragmentation and elongation are caused by excess fission and fusion, respectively [ 217 , 219 ].…”
Section: Zinc and Mitochondrial Dynamicsmentioning
confidence: 99%
“…Zinc impairment of fusion–fission dynamics likely plays an important role in causing these morphological changes, as mitochondrial fragmentation and elongation are caused by excess fission and fusion, respectively [ 217 , 219 ]. Activation of DRP1, which plays a critical role in fission [ 242 ], has been shown to contribute to mitochondrial fragmentation, and recent studies have demonstrated that zinc causes mitochondrial fragmentation via DRP1 activation in ß cells [ 239 , 240 , 243 ]. Moreover, zinc induces DRP1-mediated fission, resulting in mitochondrial fragmentation and mitochondrial network disruption in brain endothelial cells [ 241 ].…”
Section: Zinc and Mitochondrial Dynamicsmentioning
confidence: 99%
“…Zinc causes mitochondrial morphology changes such as mitochondrial fragmentation, evidenced by the formation of small, round mitochondrial puncta [233][234][235][236]. Zinc impairment of fusion-fission dynamics likely play an important role in causing these morphological changes, as mitochondrial fragmentation and elongation are caused by excess fission and fusion, respectively [212,214].…”
Section: Fission Fusion and Morphologymentioning
confidence: 99%
“…Zinc impairment of fusion-fission dynamics likely play an important role in causing these morphological changes, as mitochondrial fragmentation and elongation are caused by excess fission and fusion, respectively [212,214]. In fact, activation of DRP1, which plays a critical role in fission [237], has been shown to contribute to mitochondrial fragmentation, and recent studies have demonstrated that zinc causes mitochondrial fragmentation via DRP1 activation in ß cells [234,235,238]. Moreover, zinc induces DRP1-mediated fission, resulting in mitochondrial fragmentation and mitochondrial network disruption in brain endothelial cells [236].…”
Section: Fission Fusion and Morphologymentioning
confidence: 99%